Reduction in systemic muscle stress markers after exercise-induced muscle damage following concurrent training and supplementation with specific collagen peptides – a randomized controlled trial - Bischof, Kevin; Stafilidis, Savvas; Bundschuh, Larissa; Oesser, Steffen; Baca, Arnold; König, Daniel (Frontiers in Nutrition, 2024)
Collagen peptide supplementation in conjunction with exercise has been shown to improve structural and functional adaptations of both muscles and the extracellular matrix. This study aimed to explore whether specific collagen peptide (SCP) supplementation combined with a concurrent training intervention can improve muscular stress after exercise-induced muscle damage, verified by reliable blood markers.Methods: 55 sedentary to moderately active males participating in a concurrent training (CT) intervention (3x/week) for 12 weeks were administered either 15 g of SCP or placebo (PLA) daily. Before (T1) and after the intervention (T2), 150 muscle-damaging drop jumps were performed. Blood samples were collected to measure creatine kinase (CK), lactate dehydrogenase (LDH), myoglobin (MYO) and high-sensitivity C-reactive protein (hsCRP) before, after, and at 2 h, 24 h and 48h post exercise.Results: A combination of concurrent training and SCP administration showed statistically significant interaction effects, implying a lower increase in the area under the curve (AUC) of MYO (p=0.004, ηp²=0.184), CK (p=0.01, ηp²=0.145) and LDH (p=0.016, ηp²=0.133) in the SCP group. On closer examination, the absolute mean differences (ΔAUCs) showed statistical significance in MYO (p=0.017, d=0.771), CK (p=0.039, d=0.633) and LDH (p=0.016, d=0.764) by SCP supplementation.In conclusion, 12 weeks of 15 g SCP supplementation combined with CT intervention reduced acute markers of exercise-induced muscle damage and improved post-exercise regenerative capacity, as evidenced by the altered post-exercise time course. The current findings indicate that SCP supplementation had a positive effect on the early phase of muscular recovery by either improving the structural integrity of the muscle and extracellular matrix during the training period or by accelerating membrane and cytoskeletal protein repair.